SERTIFIKASI TANAH, KEPASTIAN HAK, DAN IMPLIKASINYA TERHADAP AKSES MODAL SERTA KESEJAHTERAAN EKONOMI: STUDI LITERATUR - Loso Judijanto (BORJUIS: JURNAL OF ECONOMY, 2025)
This study aims to examine the role of land certification in providing certainty of land rights and its implications for improving access to capital and economic welfare of the community. Through a literature review, this study examines various literature discussing the relationship between land ownership legality, ease of access to credit through land certificate collateral, and the resulting socio-economic impacts. The findings indicate that land certification is an important instrument in strengthening legal certainty, which in turn opens up broader opportunities for the community, particularly farmers and micro, small, and medium-sized enterprises, to obtain formal business capital. This ease of access to capital contributes significantly to increased productivity, asset value, and economic welfare of certificate holders. However, there are administrative and social barriers that need to be addressed to ensure that the benefits of land certification are felt optimally and inclusively. This study provides important recommendations for the government and stakeholders in developing policies that support the effective and sustainable implementation of land certification.